2018
DOI: 10.1097/ncq.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Multifaceted Delirium Screening, Prevention, and Treatment Initiative on the Rate of Delirium Falls in the Acute Care Setting

Abstract: Delirium is a potentially modifiable fall risk factor, but few studies address the effects of delirium programs on falls. Beginning in 2011, we implemented a nursing-driven hospitalwide delirium program targeting improvements in risk identification, prevention, detection, and treatment. Over the course of the program, delirium falls decreased from 0.91 to 0.50 per patient day (P = .0002). A decrease in overall falls was also noted (P = .0007).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 21 publications
1
41
0
1
Order By: Relevance
“…Similar to frailty, delirium cannot be regarded as an isolated mental disorder, and there is some evidence that it affects motor function as well [26]. The impaired mobility occurring during delirium may be the sign of a complex system being close to failure, as has been demonstrated in many acute care units for older hospitalized inpatients [78, 79, 80]. Frailty reflects the life-long accumulation of physical and cognitive deficits, thus defining the greater or lesser extent of an individual's vulnerability [81].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to frailty, delirium cannot be regarded as an isolated mental disorder, and there is some evidence that it affects motor function as well [26]. The impaired mobility occurring during delirium may be the sign of a complex system being close to failure, as has been demonstrated in many acute care units for older hospitalized inpatients [78, 79, 80]. Frailty reflects the life-long accumulation of physical and cognitive deficits, thus defining the greater or lesser extent of an individual's vulnerability [81].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, five were quality improvement (Babine, Farrington, & Wierman, 2013;Beasley & Patatanian, 2009;Healey et al, 2014;Isaac et al, 2018;Maia, Cruz, Shimoda, Sichieri, & Iida, 2018). (Ang et al, 2011;Ferguson et al, 2018;Groshaus et al, 2012;Toye et al, 2017; Wong Shee et al, 2014) and poorly reported intervention adherence (Ang et al, 2011;Groshaus et al, 2012;Toye et al, 2017) was a methodological issue for most studies. A detailed report of the research study quality is found in Appendix S2.…”
Section: Re Sultsmentioning
confidence: 99%
“…In one quality project that recorded falls in people with dementia, the TOP5 toolkit offered a communication intervention whereby family carers of people living with dementia share up to five essential strategies that can assist health staff to provide person-centred care (Isaac et al, 2018). In some projects, when older people with cognitive impairment were a subgroup of the sample or project population, patient education was extended to include the family (Ang et al, 2011;Ferguson et al, 2018;Maia et al, 2018). Engagement with family in care may offer new insights into how to prevent falls in older people with cognitive impairment.…”
Section: Engaging With Families In Falls Preventionmentioning
confidence: 99%
See 2 more Smart Citations